Younger Vancouver Sculptors. - Balkind, Alvin (Vancouver : University of British Columbia, 1968)
Arnold, Robert ; Capel Doray, Audrey ; Falk, Gathie ; Fisher, Brian ; Grauer, Sherry ; Lewis, Glenn ; McWilliams, Allan ; Morris, Michael ; N.E. Thing Co. Pfeifer, Bodo ; Bartlett Ross, Richard ; Schmidt, Marianna ; Tanabe Takao
Younger Vancouver Sculptors, Fine Arts Gallery - The University of British Columbia, Vancouver, from October 15 through November 2, 1968. Selections from the exhibition will be circulated to: School of Art, University of Manitoba ; Department of Art, University of Alberta, Edmonton ; Regina Public Library
English
kunstcatalogus
Keywords: Vancouver